The IRA under Moss Twomey 1926-1936 - Hanley, Brian (Trinity College (Dublin, Ireland). Department of History, 2002)
This thesis is an examination of the Irish Republican Army in the post revolutionary era. Despite its defeat in the Civil War the IRA could still count its membership in several thousand by the late 1920s. It remained a force that both states in Ireland had to reckon with. However the IRA aimed not to be an effective terrorist organisation but a mass revolutionary army. I have examined the relationship between the organisation and its allies and enemies. I locate its position in broader nationalist culture and argue against previous interpretations of its social radicalism. I argue that the IRA represented a radical force, influenced by both its own members’ experiences and contemporary political philosophies.
Keywords: Modern History, Ph.D.; Ph.D. Trinity College Dublin